Robust test automation using contextual clues - Yandrapally, Rahulkrishna; Thummalapenta, Suresh; Sinha, Saurabh; Chandra, Satish (ISSTA 2014: Proceedings of the 2014 International Symposium on Software Testing and Analysis, 2014)
Despite the seemingly obvious advantage of test automation, significant skepticism exists in the industry regarding its cost-benefit tradeoffs. Test scripts for web applications are fragile: even small changes in the page layout can break a number of tests, requiring the expense of re-automating them. Moreover, a test script created for one browser cannot be relied upon to run on a different web browser: it requires duplicate effort to create and maintain versions of tests for a variety of browsers. Because of these hidden costs, organizations often fall back to manual testing. We present a fresh solution to the problem of test-script fragility. Often, the root cause of test-script fragility is that, to identify UI elements on a page, tools typically record some metadata that depends on the internal representation of the page in a browser. Our technique eliminates metadata almost entirely. Instead, it identifies UI elements relative to other prominent elements on the page. The core of our technique automatically identifies a series of contextual clues that unambiguously identify a UI element, without recording anything about the internal representation. Empirical evidence shows that our technique is highly accurate in computing contextual clues, and outperforms existing techniques in its resilience to UI changes as well as browser changes.